ROLE OF Gd³⁺: Ag CO-DOPING ON STRUCTURAL AND OPTICAL PROPERTIES OF LEAD TELLURITE GLASS CERAMICS - BOSCA, M.; CULEA, E.; BOLUNDUT, L.; PASCUTA, P.; POP, V.; TOTHAZAN, N.; VIDA-SIMITI, I. (Studia Universitatis Babeș-Bolyai Physica, 2015)
Fourier transform infrared (FTIR) and diffuse reflectance ultraviolet–visible (DR-UV-VIS) spectroscopies were used to investigated the lead tellurite glass ceramics doped with different contents of Gd3+ ions and co-doped with fixed amounts of Ag2O or metallic Ag nanoparticles (AgNPs). FTIR spectral studies have been made to put in evidence the presence of basic structural units in the studied glass ceramics samples. The obtained FTIR spectra reveal vibrational IR bands which are attributed to the presence of TeO3, TeO4, PbO3 and PbO4 structural units in the glass ceramics network. DR-UV–VIS spectra were used to calculate the optical band gap energy (Eg). The obtained Eg values depend on the Gd3+ ions content and the nature of the co-dopant (Ag2O or AgNPs) present in the studied glass ceramics samples.